PROSPEK KEADILAN RESTORATIF DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Cholida Hanum (VERITAS, 2021)
This study aims to examine the concept of restorative justice from the point of view of Indonesian legislation. So far, studies on restorative justice have been limited to criminal law studies alone, so it is interesting to later portray restorative justice from a statutory perspective which is part of the study of constitutional law. Based on the author's investigation, the adoption of the concept of restorative justice in Indonesia is relatively new, which began after the DPR passed Law No. 11 of 2012 on an integrated criminal justice system. This law, although it was formed in 2012, came into effect two years later, namely in 2014. Restorative justice in the SPPA Law is enforced by a diversion method, namely the process of transferring children's cases from the judicial process to outside the court. There are at least two derivative regulations to carry out the mandate of the SPPA Law, first, the Supreme Court Regulation Number 4 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Justice System and second, the Republic of Indonesia Attorney's Regulation Number 15 of 2020 concerning Cessation of Prosecution Based on Restorative Justice. Abstrak Penelitian ini berusaha mengkaji konsepsi keadilan restoratif dalam sudut pandang peraturan perundang-undangan di Indonesia. Selama ini kajian mengenai keadilan restoratif terbatas pada kajian hukum pidana semata sehingga menarik untuk kemudian memotret keadilan restoratif dari perspektif perundang-undangan yang mana menjadi bagian dari kajian hukum tata negara. Berdasarkan penelusuran penulis, pengadopsian konsep keadilan restoratif di Indonesia terbilang baru yakni dimulai pasca DPR mensahkan Undang-undang Nomor 11 tahun 2012 tentang Sistem Peradilan pidana terpadu. Yang mana undang-undang ini meskipun dibentuk pada tahun 2012 namun mulai berlaku dua tahun kemudian yaitu pada tahun 2014. Keadilan restoratif dalam UU SPPA diberlakukan dengan metode diversi yaitu proses pengalihan perkara anak dari proses peradilan menjadi di luar peradilan. Setidaknya terdapat dua peraturan turunan guna melaksanakan amanah UU SPPA ini pertama, Peraturan Mahkamah Agung Nomor 4 Tahun 2014 tentang Pedoman Pelaksanaan Diversi dalam Sistem Peradilan Anak dan kedua, Peraturan Kejaksaan Republik Indonesia Nomor 15 tahun 2020 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif.